सकर्मकत्वाकर्मकत्वविमर्श: - Gautam, Nagendra (Haimaprabha, 2025)
This article focuses on the combination of the characteristics of Kauṇḍa, Bhatta and Nāgeśa regarding the active and passive participles. In the eighth chapter, Maharshi Panini has taught ten formulas, such as "from the infinitive," which use the infinitive. There is one formula used for the active participle, "Udaschara: from the active participle. In accepting the general characteristics of the active and passive participles, the verb jivdhatu is active because it is accompanied by the action in the form of life, but it is desired to be passive. Thus, since the literature on the form of the verb of the month in 'masam asyate' does not mean that there is no absence of action in the verb asdhatu, it would not be non-verbal. For this reason, grammarians such as Kaundabhatta and others argue that the transaction denoting the transaction of the distinction between the meaning and the fruit of the substantive is active, and that the transaction denoting the transaction of the equivalent of the substantive, the meaning and the fruit is passive. Nagesh Bhatta, on the other hand, argues that the consequential meaning of the word-scriptural action is active, and the consequential meaning of the word-scriptural action is non-verbal. That is why in 'adhyasita bhumaya:' the preposition asdhatu is proved to be active. Otherwise, when the characteristic specified by the ancients is accepted, the adhi+as+kta (used in the action) is the infinitive, and therefore the suffix kta would be the second of the word adhyasita, since the action is not stated. Thus, there is nothing wrong with accepting the scriptural characteristics of the word Nāgeśābhima. The graph at the end makes everything coherent. It is expected that this article will be helpful to those who are curious to study the subject of active and passive.